Can Tax Compliance Research Profit from Biology? - Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2014)
Historically, tax compliance has been a highly interdisciplinary avenue of research to which economics, psychology, law, sociology, history, political science, and accountancy have made valuable contributions. It is less well understood, however, whether we can glean useful insights into tax compliance by moving beyond the social sciences. In particular, the literature pays little attention to the relevance of biology. This paper attempts to remedy this shortcoming by examining the potential opportunities and limitations of introducing biological concepts into tax compliance research.
Keywords: H26; B40; B52; C63; D03; Z19; 330; tax compliance; tax morale; tax evasion; biology; genetics